Some Common Fixed Point Theorems in Partial Metric Spaces - Erdal Karapınar; Uğur Yüksel (Journal of Applied Mathematics)
Many problems in pure and applied mathematics reduce to a problem of common fixed point of some self-mapping operators which are defined on metric spaces. One of the generalizations of metric spaces is the partial metric space in which self-distance of points need not to be zero but the property of symmetric and modified version of triangle inequality is satisfied. In this paper, some well-known results on common fixed point are investigated and generalized to the class of partial metric spaces.